EFISIENSI USAHATANI PADI DI KABUPATEN MERAUKE - Marthen Nahumury (AGRICOLA, 2013)
Research efficiency in rice farming is done by taking a sample of Merauke District in Sloping Land District and represented by five villages namely Yasa Maru Village, Village Waninggap Miraf, New Life Village, Village Amungkay, and Village Yaba Maru using as many as 51 respondents were selected at random (simple random sampling). This study aims to analyze the use of factors of production of rice farming, rice farming scale analyzes and analyze the efficiency of rice farming village in the district of Merauke Sloping Land. Research results showed that at the same factors of production (land, labor, seeds, fertilizers, and pesticides) affect rice production in the district of Merauke, Merauke rice farming on an increasing scale (increasing returns to scale) means that the scale of farming rice in Merauke managed inefficient farmers with arable land area of 1 ha. To get the level of efficiency, farmers are able to manage with the small size of arable land or small scale (<1 ha) given the conditions of rice farming in Merauke on an increasing scale (increasing returns to scale). There is no factor that paddy production reached a level of economic efficiency, so as to increase rice production in Merauke required optimizing the use of production factors efficiently. Based on the level of efficiency, production input of labor, seeds, fertilizers and pesticides to be added in order to obtain maximum production given the large-scale land requires the addition of each input on rice production in the district of Merauke